Estimation of D-dimer levels in COVID-19 patients and its correlation with age and gender - Chander, Kalash (International Journal of Advances in Medicine, 2021)
Background: COVID-19 patients show some kind of abnormal coagulation parameters, related to thrombotic disorders, which can act as marker of the disease. One such marker is D-dimer, which is a widely used fibrin degradation product test used for initial diagnosis of thrombotic disorders. D-dimer levels from patients coming in OPD of sub-district hospital Bishnah, Jammu were analyzed to estimate the degree of this relation to its severity, age and gender. Methods: A retrospective study was conducted on the D-dimer data, collected from the patients coming in OPD of sub-district hospital Bishnah, Jammu, from March 2019 to March 2020. Randomly selected 134 patients infected with COVID-19, with known age and gender and confirmed by RT-PCR were included in the study. Results: Out of these 134 patients, 76 were males (56.72%) and 58 were females (43.28%). 41.04% patients belonged to the age group 51 to 70 years; 92 patients had elevated levels of D-dimer levels, 52 (38.8%) patients showed D-dimer levels four-folds the safe level, >1000 ng/ml and a significant number of females (70.7%) were found to be with elevated D-dimer levels. Women were found to be at a higher risk of developing thrombotic disorders than men. There was slight relation of thrombotic disorders such as D-dimer with postmenopausal age of women as well. Conclusions: This study has shown a clear guidance that women and older individuals are at a higher risk of developing thrombotic disorders during COVID-19 infection.